Carbazate modified dextrans as scavengers for carbonylated proteins. (15th March 2020) - Zhou, Bo; Gao, Ming; Feng, Xianjing; Huang, Lanli; Huang, Quanxin; Kootala, Sujit; Larsson, Tobias E.; Zheng, Li; Bowden, Tim
Highlights: Novel functionalized dextrans were fabricated by the reaction with hydrazine. Modified dextrans could specifically screen the carbonyls and block their toxicity. Scavenging effects were achieved by click chemistry between carbazate and carbonyls. The functionalized dextrans might be applied as nanosized scavengers of ROS. Abstract: A series of biocompatible and non- toxic polysaccharide molecules have been successfully fabricated and explored their potential application for scavenging the carbonyl species in vitro. These macromolecules were dextrans with different hydrazide substitution ratios determined by TNBS assay, NMR and FTIR characterization. The colorimetric assay had demonstrated that these macromolecules could effectively scavenge acrolein, oxidized bovine serum albumin (BSA) in buffer solutions as well as carbonyl proteins from serum. The scavengers could achieve twice more scavenging effects for modified dextrans with high molecular weight (Mw = 100, 000) than those of low ones (Mw = 40, 000) with the same substitution ratio. Protein gel electrophoresis confirmed that the formation of the complex between carbonyls and modified dextrans resulted in appearance of slower bands. It also revealed that such macromolecules could protect cultured cells against the toxicity of acrolein or its derivatives. The proposed macromolecules indicated a very promising capability as scavengers for oxidative stress plus its derivatives without side effects.